Loss of smooth muscle SDF-1/CXCL12 leads to cardiac hypertrophy and aortic valve stenosis. (25th November 2020) - Ghadge, S.K; Messner, M; Seiringer, H; Zeller, T; Boernigen, D; Weninger, W.J; Geyer, S.H; Sopper, S; Poelzl, G; Tepekoeylue, C; Zaruba, M.M
Abstract: Background: Stromal cell-derived factor-1 (SDF-1 or CXCL12) and its receptors CXCR4/CXCR7 have prominent role in cardiovascular development and myocardial repair following ischemic injury. Nevertheless, detailed mechanisms of the cell specific role of SDF-1 are poorly understood. Since SDF-1-EGFP lineage tracking revealed high expression of SDF-1 in smooth muscle cells, we aimed to investigate the cell specific role by generating a smooth muscle cell specific SDF-1 (SM-SDF-1−/−) knockout mouse model. Methods: SDF-1 expression was analyzed utilizing SDF-1-EGFP reporter mice. Conditional SM-SDF-1 KO mice were generated using Tagln-Cre; SDF-1fl/fl mice. Hearts were analysed with histology and high-resolution episcopic microscopy. Cardiac function was assessed utilizing echocardiography. RNAseq, qRT-PCR, flow cytometry and western blotting were performed. Cardiac fibrosis, apoptotic index, cell proliferation, aortic valve calcification were analyzed. SM-SDF-1−/− mice were treated with the CXCR7 agonist TC14012 (10mg/kg/I.P). Results: SDF-1-EGFP lineage tracking and immunofluorescence revealed high expression of SDF-1 particularly in smooth muscle cells and less frequently in perivascular and endothelial cells. Conditional SM-SDF-1−/− mice showed a high pre- and perinatal mortality (50%). Immunohistochemistry of SM-SDF-1−/− mice revealed severe cardiac hypertrophy, associated with increased cardiac fibrosis, apoptotic cell death, thinned and dilated arteries and significantly decreased M2 like CD11b+/CD206+ cells. Echocardiography confirmed concentric hypertrophy, with decreased stroke volume. As a possible reason for cardiac hypertrophy, SDF-1 mutants exhibited aortic stenosis due to aortic valve thickening associated with downregulation of the SDF-1 co-receptor CXCR7. We further noticed increased plasma levels of SDF-1 in aortic stenosis patients suggesting a cardioprotective role. Transcriptome analyses from KO hearts showed an abnormal extracellular matrix (ECM) remodelling with a specific upregulation of the important valve related proteoglycans Versican, Glycan. Western blot analysis revealed activation of AKT and ERK, whereas CXCR7 expression was significantly downregulated in KO mice. To rescue the phenotype we treated KO mice with the CXCR7 agonist (TC14012) which partially attenuated aortic valve remodelling through activation of the ERK signalling pathway. Conclusion: Our data suggest that SDF-1 is critically involved in maintaining the homeostasis of the aortic valve by regulating CXCR7 signalling. Pharmacological activation of CXCR7 might be a promising therapeutic target to limit the progression of aortic valve stenosis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Austrian Science Fund, Austrian research promotion agency